Factor Structure and Validity of the Japanese Version of the Emotional Availability Self-Report - Nozomi Kanehira; Young Ae Kang; Eriko Suwa; Sugako Asaeda; Toshihiko Tsutsumi; Keiko Tsuji; Koudai Fukudome; Mina Nakano; Masamichi Yuzawa (Children)
Background/Objectives: Emotional interactions between mothers and children are essential for later developmental outcomes such as children’s health, social competence, and language skills. However, an observational assessment of such interactions cannot reveal how mothers perceive their relationships with their children. Therefore, in this study, we translated and validated the Japanese version of the Emotional Availability Self-Report (EA-SR-J) and examined its factor structure, reliability, and validity. Methods: The participants were 739 Japanese mothers with children aged from 1 month to 5 years and 11 months. Results: Exploratory factor analysis revealed 19 items and four factors (Affect Quality, Hostility, Mutual Attunement, and Child Involvement with Parent) for the EA-SR-J. However, Intrusiveness was removed, and some items were assigned to different factors compared with the original scale. Cronbach’s alpha of each subscale ranged from 0.81 to 0.88, indicating sufficient internal consistency. The convergent validity of the scale was confirmed with expected correlations with variables related to attachment and child-rearing style. Discriminant validity was confirmed by group differences in variables related to children’s autism spectrum disorder symptoms and mothers’ depression symptoms. Conclusions: Although the EA-SR-J contains fewer items than the original scale, with the Intrusiveness item removed, it remains a reliable and valid tool. Further studies using the Emotional Availability Scale based on observation are needed in the future.